The role of the hadron-quark phase transition in core-collapse supernovae. Issue 2 (22nd August 2022) - Jakobus, Pia; Müller, Bernhard; Heger, Alexander; Motornenko, Anton; Steinheimer, Jan; Stoecker, Horst
ABSTRACT: The hadron-quark phase transition in quantum chromodynamics has been suggested as an alternative explosion mechanism for core-collapse supernovae. We study the impact of three different hadron-quark equations of state (EoS) with first-order (DD2F_SF, STOS-B145) and second-order (CMF) phase transitions on supernova dynamics by performing 97 simulations for solar- and zero-metallicity progenitors in the range of 14-100 M_ . We find explosions only for two low-compactness models (14 and 16 M_ ) with the DD2F_SF EoS, both with low explosion energies of 10^50 erg . These weak explosions are characterized by a neutrino signal with several minibursts in the explosion phase due to complex reverse shock dynamics, in addition to the typical second neutrino burst for phase-transition-driven explosions. The nucleosynthesis shows significant overproduction of nuclei such as 90 Zr for the 14- M_ zero-metallicity model and 94 Zr for the 16-M_ solar-metallicity model, but the overproduction factors are not large enough to place constraints on the occurrence of such explosions. Several other low-compactness models using the DD2F_SF EoS and two high-compactness models using the STOS EoS end up as failed explosions and emit a second neutrino burst. For the CMF EoS, the phase transition never leads to a second bounce and explosion. For all three EoS, inverted convection occurs deep in the core of the protocompact star due to anomalous behaviour of thermodynamic derivatives in the mixed phase, which heats the core to entropies up to 4 k B /baryon and may have a distinctive gravitational-wave signature, also for a second-order phase transition.